IMPLEMENTATION OF ISLAMIC BOARDING SCHOOL BASED PRISON PERSONALITY DEVELOPMENT IN CLASS IIA CORRECTIONAL INSTITUTION IN PADANG - Fauzan Fauzan; Denny Nazaria Rifani (Polteknik Ilmu Pemasyarakatan, 2020)
This research discusses the personality development with islamic boarding school based that carried out in the Class IIA Padang Correctional Institution. The goal is to make prisoners not only as religious people but also human beings who understand and practice their religious rules. The essence produced from this guidance is a behavior improvement factor that makes prisoners become prisoners who are not physically healthy but also spiritually healthy where the prisoner can improve and reform their actions and behavior so that they have a healthy personality, commendable character and are responsible for carrying out their actions. life. This research uses qualitative research methods with interview data techniques, observation and literature research. The results showed that there was a clear islamic boarding school based coaching organizational structure, had internal and external teaching staff who ran the program in accordance with technical instructions and implementers and had learning materials such as Ummul Qur'an and fiqih. In its application, prisoners will participate in this program starting from Monday-Saturday for 3 hours a day provided that the prisoners have met the predetermined requirements. The implementation of islamic boarding school based personality development has run quite well in terms of three aspects, namely organization, interpretation and application.